Intention to consume halal food and its impact on physical well being: Evidence from Tasikmalaya - Friantoro, Dian; Andani, Listia; Ramadhan, Rifky Wahyu (LPMP Imperium, 2025)
This study aims to identify the factors influencing the intention to consume halal food and to assess its impact on physical well-being. The research is framed within the Theory of Planned Behavior (TPB), which includes constructs such as attitude, subjective norms, perceived behavioral control, religiosity, food safety, nutritional quality, and behavioral intention, along with their effects on individual physical well-being. The analysis employs Structural Equation Modeling-Partial Least Square (SEM-PLS). It is based on responses from 307 participants in Tasikmalaya, West Java. The main finding reveals that religiosity, food safety, and nutritional quality do not significantly influence a Muslim's choice to consume halal food. This implies that the behavior surrounding halal food consumption is not necessarily dependent on religious beliefs, food safety, or nutritional content. Nonetheless, halal food consumption behavior can substantially positively impact the physical well-being of Muslims. Public interest statements This research is important for society as it highlights the role of consuming halal food in promoting physical well-being. This finding is valuable for both consumers and food producers. It underscores the health benefits of consumers choosing halal food beyond religious reasons. For producers and policymakers, the research stresses the need to improve access to affordable halal food and promote its health benefits, potentially leading to healthier communities.